2009
DOI: 10.1504/ijlsm.2009.022506
|View full text |Cite
|
Sign up to set email alerts
|

A Porter-SCOR modelling approach for the hospital supply chain

Abstract: We suggest in this paper a modelling approach that extends the Analysis Specification Conception and Implementation (ASCI) methodology by putting the accent on the performance dimension. We suggest a value model as an extension of ASCI methodology based on Porter's and SCOR models. We underline the necessity of defining an appropriate system of performance metrics that should be defined in accordance with the hospital value system. This extended methodology provides the user with a better understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Di Martinelly et al [46] apply the Supply Chain Operations Reference (SCOR) model together with Porter's value chain modeling approach to the hospital supply chain and define reliability, responsiveness, flexibility, costs and assets to be five types of performance metrics. De Pourcq et al [8] use a Balanced Score Card (BSC) model to develop a process-oriented performance measurement system to integrate business functions throughout supporting processes within the hospital.…”
Section: Performance Measurement Framework In a Hospital Contextmentioning
confidence: 99%
“…Di Martinelly et al [46] apply the Supply Chain Operations Reference (SCOR) model together with Porter's value chain modeling approach to the hospital supply chain and define reliability, responsiveness, flexibility, costs and assets to be five types of performance metrics. De Pourcq et al [8] use a Balanced Score Card (BSC) model to develop a process-oriented performance measurement system to integrate business functions throughout supporting processes within the hospital.…”
Section: Performance Measurement Framework In a Hospital Contextmentioning
confidence: 99%
“…SCOR model resulted from the consensus between several industry leaders and is therefore adapted to the supply chain requirement of a broad variety of industries and applications (Supply Chain Council, 2012). It calls upon standard processes and performance indicators which provides the standards needs to communicate and enabling benchmarking (Di Martinelly et al, 2009). This permits to enhance comparability and put the evaluation of city logistics initiatives in a context of the evaluation of best practices across supply chains.…”
Section: Relevance Of the Scor Model For Assessing Urban Consolidatiomentioning
confidence: 99%
“…However, it has been identified that the SCOR model needs to be adapted to different environmental settings in order to reap the benefit. Examples exist where the model has been adapted to after-sales industries (Legnani 2011) and healthcare industries (di Martinelly et al 2009). …”
Section: The Scor Modelmentioning
confidence: 99%